Integrated Water Resources Management to Realize Sustainable Development Goals According to Law Number 17 of 2019 and The Perspective of Fiqh Bi’ah - Pininta, Agniski; Jundiani, Jundiani; Lutfi, Mustafa (Al-Balad: Journal of Constitutional Law, 2024)
The increasing population has led to a growing demand for water. The declining quality and limited availability of clean water support this problem. This research examines the issue of integrated water resources management and the concept of sustainable development goals. This research uses normative juridical analysis. The approach used is a statutory approach and a conceptual approach that will be harmonized with the provisions of the legislation. This research uses primary data sources and secondary data. This study shows that integrated water resources management is regulated in Indonesian Law No. 17 of 2019, which aims to utilize water resources sustainably, with the main priority being the fulfilment of water for the basic daily needs of the community to achieve sustainable development goals. This integrated water resources management activity with sustainable principles has not been able to reduce the number of clean water and sanitation crises due to the lack of institutional optimization and awareness of the responsibilities and roles of all stakeholders, which still need to be improved. In the context of Fiqh Bi'ah, several ways can help achieve Sustainable Development Goals: the prohibition of water waste, efforts to maintain water ecosystems, and a ban on water pollution.